2013
DOI: 10.1097/pas.0b013e318289c765
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Gata3 and Phox2b Expression in Tumors of the Autonomic Nervous System

Abstract: Autonomic neurons and chromaffin cells, which constitute the autonomic nervous system, are derived from a common progenitor from the neural crest, and its development is controlled by a network of transcription factors, including the master regulator, Phox2b, and its downstream, Gata3. Anti-Phox2b and anti-Gata3 antibodies were applied to a total of 77 autonomic nervous system tumors, including 35 paragangliomas, 21 pheochromocytomas, 9 neuroblastomas, 4 ganglioneuroblastomas, and 8 ganglioneuromas, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
65
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 23 publications
3
65
1
Order By: Relevance
“…In this setting, a panel of site-specific lineage markers (TTF-1 for pulmonary origin, CDX2 for gastrointestinal tract origin, PAX8/PAX6 for gastropancreatic and duodenal origin, and ER/PR, mammaglobin, GCDFP-15 and GATA3 for mammary origin) may be helpful in distinguishing metastatic neuroendocrine neoplasms (particularly well-differentiated neuroendocrine tumors) from invasive mammary carcinomas with neuroendocrine differentiation. [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] In this study, CDX2 was positive in all examined metastatic neuroendocrine neoplasms of small bowel origin, TTF-1 was positive in 70% of examined metastatic neuroendocrine neoplasms of lung origin, and ER and GATA3 were positive in 91 and 100% of invasive mammary carcinomas with neuroendocrine differentiation, respectively. Similarly, in the study by Perry et al 9 (which with the exception of one high-grade neuroendocrine carcinoma consisted entirely of well-differentiated neuroendocrine tumors), all metastatic neuroendocrine neoplasms from the gastrointestinal tract expressed CDX2 and 60% of tumors originating from the lung expressed TTF-1.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this setting, a panel of site-specific lineage markers (TTF-1 for pulmonary origin, CDX2 for gastrointestinal tract origin, PAX8/PAX6 for gastropancreatic and duodenal origin, and ER/PR, mammaglobin, GCDFP-15 and GATA3 for mammary origin) may be helpful in distinguishing metastatic neuroendocrine neoplasms (particularly well-differentiated neuroendocrine tumors) from invasive mammary carcinomas with neuroendocrine differentiation. [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] In this study, CDX2 was positive in all examined metastatic neuroendocrine neoplasms of small bowel origin, TTF-1 was positive in 70% of examined metastatic neuroendocrine neoplasms of lung origin, and ER and GATA3 were positive in 91 and 100% of invasive mammary carcinomas with neuroendocrine differentiation, respectively. Similarly, in the study by Perry et al 9 (which with the exception of one high-grade neuroendocrine carcinoma consisted entirely of well-differentiated neuroendocrine tumors), all metastatic neuroendocrine neoplasms from the gastrointestinal tract expressed CDX2 and 60% of tumors originating from the lung expressed TTF-1.…”
Section: Discussionmentioning
confidence: 97%
“…GATA3 expression is well recognized in breast carcinomas and urothelial carcinomas and more recently has also been described in a variety of other tumors, including (but not limited to) certain renal epithelial tumors, cutaneous squamous cell carcinomas, certain skin adnexal and salivary gland tumors, mesotheliomas, and autonomic nervous system tumors such as paragangliomas, pheochromocytomas, and neuroblastic tumors (neuroblastomas, ganglioneuroblastomas, and ganglioneuromas), but its expression in extramammary epithelial neuroendocrine tumors has not been described. 47,[50][51][52] Hence, GATA3 positivity in a breast tumor with neuroendocrine morphology would argue against a metastatic neuroendocrine neoplasm and in favor of a primary invasive mammary carcinoma with neuroendocrine differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown to be a regulator of and to be required in nephric (Wolffian) duct morphogenesis and guidance of the mesonephric duct (17). GATA3 has proven to be a useful immunohistochemical marker in the diagnosis of breast and urothelial carcinomas, and has been described in autonomic nervous system tumors (18,19). During the preparation of this manuscript, a study with a large cohort of different types of human neoplasms reported that GATA3 is expressed in basal cell and squamous cell carcinomas as well as adnexal tumors of the skin, trophoblastic lesions, and some germ cell tumors including choriocarcinoma and yolk sac tumors, and approximately half of chromophobe renal cell; carcinomas and mesotheliomas among other tumors with focal expression; however, it was not studied in mesonephric lesions (20).…”
Section: Discussionmentioning
confidence: 98%
“…[9][10][11][12][13][14][15] Relatively small studies looking at GATA3 expression in other tumor types revealed frequent positivity in paragangliomas, salivary gland tumors, ovarian Brenner tumors, and signet ring cell adenocarcinomas of the urinary bladder. 16,17 Less common expression has been documented in renal cell carcinomas, endometrial adenocarcinomas, and squamous cell carcinomas from the head/neck, lung, and cervix. [18][19][20][21] In a recent comprehensive analysis of GATA3 expression in human tumors, the spectrum of neoplasms commonly positive for GATA3 was expanded to include not only those previously mentioned, but also a subset of cutaneous basal cell carcinomas and other skin adnexal tumors, yolk sac tumor, choriocarcinoma, mesothelioma, pancreatic ductal adenocarcinoma, chromophobe renal cell carcinoma, oncocytoma, and the epithelial component of synovial sarcoma.…”
mentioning
confidence: 98%